Nanostructures on the ZnSe Surface: Synthesis, Morphological and Photoluminescent Properties - Suchikova, Y.; Lazarenko, A.; Kovachov, S.; Bohdanov, I. (Physics and Chemistry of Solid State, 2021)
Nanostructured zinc selenide has been obtained by electrochemical etching with an H2SO4:H2O:H2O5OH=4:1:1 solution used as the electrolyte. The experiment has indicated that the surface consists of two phases, namely the upper layer made up of a dense oxide film and a low-sized porous layer underneath, with a pore diameter of (30-80) nm and a thickness of interporous walls of (15-50) nm. The investigated dependence of surface porosity on the etching time allows us to explain the main stages of the crystal’s electrochemical dissolution during anodizing. The experiment has indicated the presence of three main stages, such as the formation of the Gouy and Helmholtz layers at the semiconductor/electrolyte segregation; pore formation at defect and oxide crystallite locations; spontaneous pore formation. The PL spectra of the samples under study have demonstrated three maxima. The emission band at 2.45 eV is attributable to the presence of oxides, the band at 2.78 EV can be accounted for the corresponding excitons while the band at 2.82 eV stems from quantum-dimensional effects. Chemical analysis of the samples has also indicated the presence of oxides on the surface of the nanostructure.